KORELASI KETERAMPILAN MEMAHAMI TEKS CERPEN DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA NEGERI 2 BATANG ANAI - Putri, Dea Denisa; Afnita, Afnita (Universitas Negeri Padang, 2019)
ABSTRACT This study had three proposes. First, describing the students’ understanding of short story of eleventh grade students of SMAN 2 Batang Anai. Second, describing the students’ writing ability of short story. Third, describing the correlation between students’ understanding short story and their writing ability of short story of eleventh grade students of SMAN 2 Batang Anai. The type of this research was quantitative with descriptive method. The design used in this study was correlational design. The population of this study was the eleventh grade students of SMAN 2 Batang Anai academic year 2018/2019, which was 195 students. The sample in this study was determined by propotional random sampling of 20% of participation, which is 40 students. The results of this study were devided into three. First, the ability to understand the short story text of eleventh grade students of SMAN 2 Batang Anai was in accordance with good qualifications (B). Second, the students’ writing ability of eleventh grade students of SMAN 2 Batang Anai in accordance with the qualifications weremore than enough (LdC). Third, there was a correlation between students’ understanding short story and their writing ability of short story of eleventh grade students of SMAN 2 Batang Anai with a degree of freedom n-1 at the level of 95% confidence. Tcount (4.50) was biggerthan t table (1.68), that was tcount> t table (4.50> 1.68) thus H0 was rejected and H1 was accepted because the test results prove that tcount was bigger than t table. Kata Kunci: korelasi, keterampian memahami teks cerpen , menulis teks cerpen